Electron Scattering: Nature of Electron Scattering in LaAlO3/SrTiO3 Interfaces Near the Critical Thickness (Adv. Mater. Interfaces 1/2015). Issue 1 (January 2015) - Li, C. J.; Lü, W. M.; Wang, X. Renshaw; Qiu, X. P.; Sun, L.; Zeng, S. W.; Liu, Z. Q.; Huang, Z.; Zhao, Y. L.; Ariando; Venkatesan, T.
<x xml:space="preserve">Abstract</x> M. Lü, T. Venkatesan, and co‐workers demonstrate in article 1400437 the percolation of two dimensional electron gases (2DEG) at the LaAlO3/SrTiO3 perovskite oxide interface. The fourth unit cell islands on top of a uniformly plane of a three unit cell of a LaAlO3 film generate 2DEG in the underneath SrTiO3 layer locally. When the island coverage ratio reaches a critical value of ca. 65%, 2DEG islands percolate to form a continuous conducting network. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>